2018
DOI: 10.21608/blj.2018.47582
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial and bio-histological effects of cerastes cerastes venom on albino mice

Abstract: Background: Snake venoms contain mixtures of proteins that have different pathological and pharmaceutical effects. In the present study, we evaluated, in vitro the anti-bacterial activity of Cerastes cerastes (C. cerastes) crude venom. Results revealed it has broad antibacterial activity against S. typhimurium and S. aureus, and resistant to E. coli. In vivo, we analyzed the biochemical and histological effects of the sublethal dose of the venom. 45 Swiss albino mice were divided into 3 groups (15 mice/ group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…They showed marked dilation and congestion of myocardial blood vessels with minor intermuscular hemorrhage in addition to slightly degenerated myocytes in C. cerastes injected groups. This agreed with Shabaan et al (2018) and Shaker et al, (2018) they reported marked dilation and congestion of myocardial blood vessel Also, Al-Mamun et al (2015) found that snake venom induced variable degrees of histopathological alterations in cardiac tissues according to injected dose. In the present study, A. mellifera injected group showed non-significant increase in CPK enzyme, which attenuated activities in A. mellifera group were possibly linked with its antioxidant properties of Melittin that protected and solidified the cell membranes from oxidative stress-initiated damage, which agreed with Sadek et al (2019).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…They showed marked dilation and congestion of myocardial blood vessels with minor intermuscular hemorrhage in addition to slightly degenerated myocytes in C. cerastes injected groups. This agreed with Shabaan et al (2018) and Shaker et al, (2018) they reported marked dilation and congestion of myocardial blood vessel Also, Al-Mamun et al (2015) found that snake venom induced variable degrees of histopathological alterations in cardiac tissues according to injected dose. In the present study, A. mellifera injected group showed non-significant increase in CPK enzyme, which attenuated activities in A. mellifera group were possibly linked with its antioxidant properties of Melittin that protected and solidified the cell membranes from oxidative stress-initiated damage, which agreed with Sadek et al (2019).…”
Section: Introductionsupporting
confidence: 87%
“…Also, Tohamy et al (2014) reported an increase in both ALT & AST enzymes in animals treated with 1/2 LD 50 of N. haje, regardless of the differences in injecting route, dose, species and time post-injection. Another study showed el-evation in the ALT & AST levels after snake envenomation, indicating that liver was primary target organ of venom (Shabaan et al, 2018). This was confirmed by some alterations in the liver histological features of injected groups as minor cytoplasmic vacuolization of hypatocytes with macro vascular fatty degeneration and minor focal hepatic hemorrhage (Shaker et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
“…Electronic spectra were recorded as Nujol mulls and/or solutions in dimethylformamide (DMF) on a Jasco model V-550 UV/Vis spectrophotometer at room temperature. Mercury-300 BB apparatus was used to record the 1 H nuclear magnetic resonance (NMR) (300 MHz) and 13 C NMR (75 MHz) spectra in dimethyl sulfoxide (DMSO)-d 6 as a solvent and tetramethylsilane (TMS) (δ) as an internal rference. The magnetic susceptibility measurements were performed with a Johnson Matthey, Alfa product, Model No.…”
Section: Measurementsmentioning
confidence: 99%
“…Pyrano [3,2-c]quinoline derivatives exist in many natural alkaloids [1] and have a diversity of pharmacological activities including antitumor, [2] anticancer, [3] antidiabetic, [4] anti-coronavirus, [5] antihypertensive, [6] antitubercular, [7] antimalarial, [8] antibacterial, [9] antimicrobial, [10] as well as photodiode fabrication, [11] thin films, [12,13] optical applications, [14] and corrosion inhibitors. [15] Metal complexes of ligands containing quinoline moiety have attracted particular interest because of their biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Quinolines represent a large family of heterocyclic compounds which find applications in design of various medicinally important compounds, and hence, much attention has been focused on the synthesis of a diversity of quinoline derivatives. [3] Pyrano [3,2-c] quinoline derivatives have been isolated from a variety of natural alkaloids [4] and have a variety of biological properties, including anticancer, [5,6] antitumor, [7] antimicrobial, [8] antibacterial, [9] antimalarial, [10] antiinflammatory, [11] antioxidant, [12] and antiplasmodial, [13] as well as photodiode fabrication, [14] thin films, [15,16] and optical applications. [17] The biological activities of metal complexes of ligands containing a quinolinone moiety appeared antibacterial, antifungal, antitumor, and anticancer properties.…”
Section: Introductionmentioning
confidence: 99%